FROM EFFICIENCY TO EMPATHY: RECONSTRUCTING TECHNOLOGY MANAGEMENT THROUGH A HUMANITIES APPROACH IN THE DIGITAL WORK ENVIRONMENT - Alfi Syukri; Darmansyah; Silvana Nurdiani; Arief Irvan; Shinta Oktavia; Ofa Yutri Kumala; Basyarul Aziz (Journal Informatic, Education and Management (JIEM), 2026)
This study examines the paradox of digital workplace transformation where efficiency-driven technologies often dehumanize workers. Using qualitative library research and content analysis, the study identifies a humanitarian crisis in automation marked by algorithmic pressure, cognitive alienation, and weak legal protection for digital workers. The findings emphasize the need to rehumanize virtual workspaces by integrating ethics, aesthetics, and algorithmic justice through digital empathy and human-centered design. The research proposes an empathetic technology management model that prioritizes human well-being alongside productivity, promotes empathy-based leadership, and strengthens humanistic digital literacy. The study concludes that shifting from efficiency to empathy requires structural, managerial, and regulatory changes, supported by technology audits, HR policy reform, leadership training, and multi-stakeholder collaboration to create a fair and humane digital work environment